Local Government Policy: Converting Agricultural Land to Housing - Suwari Akhmaddhian; Haris Budiman; Erga Yuhandra; Septian Apriditiya (Universitas Kuningan, 2021)
This study aims to determine the regulation of converting agricultural land into housing and the suitability of its implementations. This study employed a juridical empirical approach which is a research done by looking at and paying attention to applicable legal norms associated with existing facts from the problems encountered. In this case, the local government policies on converting agricultural land into housing. The findings revealed the perpetrators of the land conversion process that occur in Kuningan Regency are the landowners. Some of the causes are: social, economic, population density, and the lack of socialization of Law Number 41 of 2009. Efforts made by local government officials and related agency officials to realize sustainable food land protection are still limited to carrying out their main duties and functions. The guideline in controlling the use of space, licensing and controlling mechanisms for the implementation of development, stated in the Regional Regulation of Kuningan Regency Number 26 of 2011 on regional Spatial Planning and Regulation of the Head of the National Land Agency Number 2 of 2011 concerning guidelines for technical land considerations in controlling location permits and determining locations and permits for changes in land use. The study concluded that converting the function of agricultural land to non-agriculture in Kuningan Regency is carried out by the landowner. In addition, efforts made by local government officials and related agency officials to realize sustainable food land protection are still limited to carrying out their main duties and functions. Accordingly, it is necessary to socialize Law Number 41 of 2009 on Protection of Sustainable Food Agricultural Land and Regional Regulation of Kuningan Regency Number 26 of 2011 concerning Regional Spatial Planning continuously to the community level. Furthermore, local governments need to coordinate with the village officials to monitor the use of agricultural land and the development of housing areas. This can be done by providing socialization to village officials.